2016
DOI: 10.18844/gjflt.v6i1.806
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Efl Learners’ Reflections on Corpus-Based Language Teaching

Abstract: The aim of this study is investigating Turkish EFL learners’ reflections on corpus-based language teaching; what kind of benefits or drawbacks they have experienced during a corpus-based implementation, and what possible suggestions they can make about this particular experience of theirs. The data was collected through minute papers and semi-structured interviews; and content analysis was conducted for data analysis. The results indicated that the participants found the corpus-based instruction very effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Additionally, they stated that they needed guidance or help from the teacher in order to analyze and understand the concordance lines. These findings are in line with the findings of Simsek (2016), who found that learners agreed that concordance lines were difficult to understand. However, the learners in the current study did not think that learning the verbs via the materials was more difficult than learning them via a dictionary.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Additionally, they stated that they needed guidance or help from the teacher in order to analyze and understand the concordance lines. These findings are in line with the findings of Simsek (2016), who found that learners agreed that concordance lines were difficult to understand. However, the learners in the current study did not think that learning the verbs via the materials was more difficult than learning them via a dictionary.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, 'involvement' might have been associated with 'learning' or 'gaining' in the learners' minds, as they mostly agreed that using the materials improved their L2 phrasal-prepositional verbs knowledge, as well as boosting their confidence in learning them. These findings confirm the findings of the studies of Chan and Liou (2005) and Simsek (2016). Chan and Liou found that learners enjoyed using a bilingual concordancer in the learning of verb-noun collocations.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations